Education and Misinformation: Exploring Ophthalmology Content on TikTok - Ritu Sampige; Emily Grace Rodgers; Austin Huang; Dagny Zhu (Ophthalmology and Therapy, 2023)
Abstract Introduction With the continuous rise of social media usage, more patients are looking online for health-related information. TikTok is one of the fastest-growing video-based social media platforms, but the quality of its ophthalmologic content, at a comprehensive level, has not been previously analyzed. We aim to explore and characterize popular ophthalmology content on TikTok, including the presence of misinformation. Methods Between April 16 and May 22, 2023, 37 different ophthalmology-relevant hashtags were queried on TikTok, and the top 20 most-liked videos per hashtag were analyzed. The quality of educational videos was graded on understandability and actionability using the Patient Education Materials Assessment Tool for Audiovisual Materials (PEMAT-A/V). Trends in creator identity, content type, engagement metrics, misinformation presence, and TikTok verification status were also assessed. Results The 37 ophthalmology-related hashtags yielded 723 videos comprising 3.806 billion views. A minority of videos were created by ophthalmologists (16.9%) and eyecare providers (35.1%), while the majority were created by non-healthcare providers (55.0%). The most common types of videos identified were primarily related to personal experiences (35.8%) and education (38.0%). Amongst educational videos, mean PEMAT-A/V understandability and actionability scores were 88.1% and 50.6%, respectively. Misinformation was found in 5.4% of all videos, comprising 4.8% of all likes, 4.7% of all comments, and 11.7% of all bookmarks. Its presence was significantly correlated with content created by non-healthcare providers (p < 0.001) and received a disproportionately higher percentage of bookmarks. Conclusions This was the largest, most comprehensive evaluation of ophthalmologic content on TikTok. A significant portion of popular ophthalmologic content on TikTok is created by non-eyecare providers and contains misinformation. Our findings confirm the need for ophthalmologists to create more engaging, actionable, and factual educational content to combat misinformation adoption.